Study of impact phenomena for the design of a mobile anti-terror barrier: Experiments and finite element analyses. (July 2020) - Baragetti, S.; Arcieri, E.V.
Highlights: The impact of a pendulum hitting five obstacles with a similar mass is studied. The studied system models the crash of a vehicle into various anti-terror barriers. The combination of experiments and FEA highlights the properties the barrier needs. A powerful mobile barrier should be deformable and use water to dissipate energy. A ballast made of metals positioned in the lower part reduces the displacement. Abstract: The most important recent terrorist attacks in Europe consist of vehicles rammed into crowds. The current response to this phenomenon is the adoption of concrete barriers, whose effectiveness is still not clear. The authors of this paper have already designed an innovative mobile anti-terror barrier which combines high performance and good look. This paper explains the most significant concepts which have been used for the design of this new barrier with the help of simple models. In detail, the impact of a pendulum hitting some obstacles with a similar total mass is investigated by means of experimental tests and finite element analysis. The purpose of this study is to identify the best solution which most efficiently stops the impacting object. The results show that a powerful mobile system should be extremely deformable and use water to dissipate energy. A ballast made of metals positioned in the lower part of the anti-terror system helps to reduce the total displacement of the barrier itself.